Spatiotemporal analysis of the association between residential eviction and fatal overdose in Rhode Island - Jennifer Ahern; Magdalena Cerdá; William C Goedel; Elizabeth A Samuels; Yu Li; Alexandria Macmadu; Benjamin D Hallowell; Kathryn M Leifheit; Alexandra Skinner; Victoria Jent; Bennett Allen; Abigail R Cartus; et al. (BMJ Public Health)
Objective Policy ramifications of the COVID-19 pandemic shape the concurrent housing and overdose crises in the USA. Housing insecurity is a known risk factor for overdose, yet how residential eviction may influence fatal overdose risk is understudied. We sought to evaluate the spatiotemporal relationship between neighbourhood-level residential eviction rates and overdose mortality in Rhode Island (RI) before and during a statewide eviction moratorium in response to COVID-19.Methods We conducted an ecological study at the census tract level in RI (N=240) by modelling the association between quintiles of eviction rates and fatal overdose rates from 2016 to 2021. We applied a Bayesian spatiotemporal approach using an integrated nested Laplace approximation and adjusted for an a priori determined set of time-varying demographic and policy covariates.Results Descriptively, we observed a direct, dose–response relationship between quintiles of eviction incidence rates over the full study period and fatal overdose. Prior to the implementation of a statewide eviction moratorium, census tracts in the highest eviction quintile had increased rates of overdose mortality, relative to those in the lowest quintile (posterior mean relative rate = 1.49, 95% credible interval: 1.05 to 2.13). Associations during the periods of eviction moratorium were non-significant.Conclusion This work highlights the neighbourhood-level relationship between residential eviction and fatal overdose risk in the absence of an eviction moratorium. Enhanced investment in eviction prevention policies, such as rent relief and limitations to the circumstances under which landlords can file for eviction, may complement harm reduction efforts to reduce neighbourhood-level overdose inequalities.